Rift Valley fever virus remains infectious in milk stored in a wide range of temperatures - Dawes, B.E.; De La Mota-Peynado, A.; Rezende, I.M.; Buyukcangaz, E.K.; Harvey, A.M.; Gerken, Keli N.; Winter, C.A.; Bayrau, B.; Mitzel, D.N.; Waggoner, J.J.; Pinsky, B.A.; Wilson, W.C.; et al. (Oxford University Press, 2025)
Background: Rift Valley fever virus (RVFV) is a zoonotic arbovirus widely distributed across Africa and the Arabian Peninsula, which causes devastating epidemics affecting humans as well as ruminant livestock. The epidemiology of RVFV is difficult to disentangle, as the virus is transmitted to humans via mosquitos or direct contact with infected animals. Among these direct exposures are milking ruminants and drinking fresh milk which have been firmly established as risk factors for RVFV exposure. However, no studies to date have addressed the stability of infectious RVFV in milk.